(untitled) (Journal of the Bangladesh Chemical Society, 2012)
Chitosan-charcoal composite was applied as a media to treat tannery effluent. The composite was prepared by a simple solution-evaporation method and the morphology of the prepared composite was characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD). Adsorption of chromium (Cr) was investigated by varying the contact time between adsorbate (Cr) and composite, pH of solution and dose of composite. The concentration of Cr was determined by atomic absorption spectroscopy (AAS). Removal of Cr was found to be dependent on pH and maximum adsorption was observed at pH 4.0. The optimum dose and contact time for Cr treatment was 40 g/L and 250 minutes respectively. The results showed that prepared composite can be used efficiently for the treatment of tannery wastewater containing chromium. DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11774 Journal of Bangladesh Chemical Society, Vol. 25(1), 53-61, 2012